PELATIHAN PENGEMBANGAN PERANGKAT PEMBELAJARAN IPS BERORIENTASI PADA PERPRES NOMOR 87 TAHUN 2017 BAGI GURU MGMP IPS SMP PEKALONGAN SEBAGAI WUJUD KONSERVASI SOSIAL (Universitas Negeri Semarang, 2019)
The objectives of community service are as follows: (1) analyzing knowledge about providing training in the development of social studies learning tools oriented to Perpres Number 87 of 2017 for MGMP IPS teachers in Pekalongan Middle School as a Form of Social Conservation; (2) train IPS-oriented learning tools in Perpres Number 87 of 2017 for MGMP IPS teachers in Pekalongan Middle School. The methods for carrying out this service include outlining priority issues; detailing the justification of problems and solutions; approaching service through lectures, group discussions, questions and answers, brainstorming, and demonstrations; detail work procedures. The results of community service activities, namely community service participants, were very enthusiastic about the Presidential Regulation no. 87 of 2017 concerning Strengthening Character Education. In the second stage of service, namely implementing the Presidential Regulation No. 87 of 2017 concerning Strengthening Character Education in learning tools. The conclusion in this community service is the Development of Social Studies Learning Tools Oriented to Perpres Number 87 of 2017 For Teachers' Teachers Social Sciences MGMP Pekalongan Middle School as a Form of Social Conservation. Tujuan dalam pengabdian masyarakat sebagai berikut: (1) menganalisis pengetahuan tentang pemberian pelatihan pengembangan perangkat pembelajaran IPS berorientasi pada Perpres Nomor 87 Tahun 2017 bagi guru MGMP IPS SMP Pekalongan Sebagai Wujud Konservasi Sosial; (2) melatihkan perangkat pembelajaran IPS berorientasi pada Perpres Nomor 87 Tahun 2017 bagi guru MGMP IPS SMP Pekalongan. Metode pelaksanaan pengabdian ini antara lain memaparkan persoalan prioritas; merinci justifikasi permasalahan dan solusi; melakukan pendekatan pengabdian melalui ceramah, diskusi kelompok, tanya jawab, curah pendapat, dan demonstrasi; merinci prosedur kerja. Hasil kegiatan pengabdian masyarakat yaitu peserta pengabdian sangat antusias pada materi Perpres No. 87 Tahun 2017 tentang Penguatan Pendidikan Karakter. Pada tahap kedua pengabdian yaitu melaksanakan implementasi Perpres No. 87 Tahun 2017 tentang Penguatan Pendidikan Karakter dalam perangkat pembelajaran. Simpulan dalam pengabdian masyarakat ini yaitu terdapat Pengembangan Perangkat Pembelajaran IPS Berorientasi Pada Perpres Nomor 87 Tahun 2017 Bagi Guru MGMP IPS SMP Pekalongan Sebagai Wujud Konservasi Sosial.